Effect of Mn-Site for Al Substitution on Structural, Electrical and Magnetic Properties in La0.67Sr0.33Mn1-xAlxO3 Thin Films by Sol-Gel Method. (26th March 2014) - Abdullah, H.; Zulfakar, M. Syafiq; Chen, S. Kien
Abstract : Nanocrystalline L a 0.67 S r 0.33 M n 1 - x A l x O 3 (x = 0.00, 0.05, 0.10, 0.15, 0.20, and 0.25) thin films have been prepared on quartz substrates by sol-gel method. The structural and morphology studies were investigated via X-ray diffraction (XRD) and field emission scanning electron microscope (FESEM). XRD graph patterns show rhombohedral distorted perovskite structures. FESEM images show that the average grain size decreased as the concentration of x increased. Electrical property was investigated using four-point probe technique. Resistivity results show that metal-insulator transition (MIT) temperatures (T p ) decreased when the concentration of x increased. T p shifted to lower temperature when the concentration of x increased. The data was analyzed based on theoretical models, where the ferromagnetic resistivity is followed with the equation ρ = ρ o + ρ 2 T 2, where ρ o is due to the significance of grain boundary effects and a second-term ρ 2 T 2 appears that might be applied to the electrons scattering. In the high temperature regime ( T > T p ), the resistivity data can be well described by small polaron hopping (SPH) and variable range hopping (VRH) mechanisms. Magnetic property was investigated using a vibration sample magnetometer. All samples that were obtained showed hysteresis curve with the highest value of magnetization for sample x = 0.10 .